2006
DOI: 10.1007/s00464-005-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of preemptive analgesia with intraperitoneal instillation of bupivacaine before rather than after the creation of pneumoperitoneum for laparoscopic cholecystectomy: a randomized, double-blind, placebo-controlled study

Abstract: Preemptive analgesia with bupivacaine peritoneal instillation is much more effective for pain relief if used before creation of pneumoperitoneum. Although the effect of bupivacaine peritoneal instillation is also noticeable when used after creation of pneumoperitoneum, it confers significantly lower benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 31 publications
(30 reference statements)
2
61
1
1
Order By: Relevance
“…This may have introduced another limitation, however, since preemptive analgesia with peritoneal instillation of bupivacaine has been shown to provide superior analgesia. 19 It also appears that the analgesic benefits of NSAIDs can be optimized by continuous prophylactic administration. [20][21][22] Therefore, our patients may have experienced additional benefit if the ketorolac treatment had been extended and initiated preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…This may have introduced another limitation, however, since preemptive analgesia with peritoneal instillation of bupivacaine has been shown to provide superior analgesia. 19 It also appears that the analgesic benefits of NSAIDs can be optimized by continuous prophylactic administration. [20][21][22] Therefore, our patients may have experienced additional benefit if the ketorolac treatment had been extended and initiated preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable with studies conducted by Berczynski et al and Maestroni et al Maestroni et al also observed that pain was significantly less in patients who received ropivacaine as compared to saline before creation of pneumoperitoneum. 8,9 However, Lee et al concluded that no significant difference in abdominal pain occurred by preemptive instillation of Bupivacaine in laparoscopic cholecystectomy. 10 This lack of effect in their study might be due to small dosage of intraperitoneal Bupivacaine used (0.25% 40 ml) as compared to our study in which we used 0.5% Ropivacaine 3mg/kg The traditional approach to postoperative analgesia is to start therapy when surgery is completed and pain is experienced.…”
Section: Resultsmentioning
confidence: 99%
“…Some trials have preemptively used dextromethorphan {an NMDA (N-methyl-D-aspartate) receptor antagonist}, NSAIDS, opiods, epidural, and multimodal analgesia with positive results in reducing pain among patients (4,36,37). Other trials assessing the role of local anaesthetic given preemptively in the form of intraperitoneal instillation were also conducted where local anaesthetic agent were given intraperitoneally and compared with placebo or groups with instillation at the end of operation (31,(38)(39)(40). However, these techniques can only be conducted after extensive literature review and large-scale multi-centre trials since evidence of the use of these modalities does not appear to be supported by large number of evidence-based literatures (4,17).…”
Section: Discussionmentioning
confidence: 99%